2022
DOI: 10.3389/fpsyg.2022.883736
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self-Discrepancy on Online Behavior: A Literature Review

Abstract: People will experience self-discrepancy when they perceive their actual self is distanced from their ideal self and ought self. The perceived self-discrepancy has a significant impact on people’s online behavior. The goal of this paper is to provide an overview of the research on self-discrepancy in the Internet era through a literature review. A total of 37 papers were included in this review. First, this study presents the basic characteristic of the reviewed articles (such as research contexts, samples, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
1
2
0
3
Order By: Relevance
“…According to their studies, youngsters are suggested to provide the self-values associated with other teenagers' perceptions, social relationship, recognition, and own domains through carefully chosen usernames, language, profile pictures in their Facebook profiles are connected in order to promote their online identity. This finding is also strengthened by Hu et al (2022). In line with the study carried out by Hu et al, people can create and provide their identity in virtual world based on their wishes.…”
Section: Achievementsupporting
confidence: 68%
“…According to their studies, youngsters are suggested to provide the self-values associated with other teenagers' perceptions, social relationship, recognition, and own domains through carefully chosen usernames, language, profile pictures in their Facebook profiles are connected in order to promote their online identity. This finding is also strengthened by Hu et al (2022). In line with the study carried out by Hu et al, people can create and provide their identity in virtual world based on their wishes.…”
Section: Achievementsupporting
confidence: 68%
“…If people believe their past disclosure does not represent who they are now, they might experience self-discrepancy. According to self-discrepancy theory, the greater an individual's self-discrepancy, the more discomfort he or she will suffer, which might result in strategic behaviors adopted to reduce selfdiscrepancy (Hu et al, 2022). For example, a user might delete his or her past self-disclosure.…”
Section: One-on-one In-depth Interviewsmentioning
confidence: 99%
“…For example, a user might delete his or her past self-disclosure. Self-discrepancy is also likely to be associated with problematic online behavior (Hu et al, 2022), such as WeChat addiction. Hence, based on the themes extracted from interviews, we added new measurement items for SW on WeChat, which are shown in Table 4.…”
Section: One-on-one In-depth Interviewsmentioning
confidence: 99%
“…Попытки понять способы самовыражения личности в цифровых средах способствуют быстрому накоплению эмпирического материала о: механизмах становления социальной и личной идентичности в виртуальных сообществах (Cheng, Guo, 2015;Lee et al, 2020), формировании цифрового опыта нарративной идентичности (Breen et al, 2021), трансмиссии офлайн-и онлайн-идентичности (Koles, Nagy, 2021), влиянии аватаров на динамику идентичности (Gabbiadini et al, 2014), вкладе аддиктивного развития в структуру виртуальной идентичности (Cioban et al, 2021;Pogorelov, Rylskaya, 2022). Обсуждаются корреляты идентичности с «экранным временем» (Перегудина, 2021;Granic et al, 2020), с атрибутивными, оценочными, когнитивными, демографическими и прочими характеристиками аватаров как онлайн-самопрезентаций и цифровых профилей пользователей (Jin, 2012;Zimmermann et al, 2023), с параметрами игровой и интернет-зависимости (Lemenager et al, 2020), с поведенческими характеристиками онлайн-активности в виртуальных сообществах (Hu et al, 2022;Crisanto et al, 2022;Santa Mar a et al, 2022), с разнообразием интернет-активности (Raiziene et al, 2022), с нейробиологическими функциями (Lemenager et al, 2020). Исследователи касаются роли процессов ясного самосознания и самооценки (Green et al, 2021;Lemenager et al, 2020;Müller, Bonnaire, 2021), инициативности поведения и деятельности (Cheng, Guo, 2015;Zimmermann et al, 2023), «расширения самости» (Belk, 2016;Koles, Nagy, 2021) в становлении идентичности в виртуальной среде.…”
Section: мв клементьева оценка статусов виртуальной идентичностиunclassified
“…Актуальность проблема психологических механизмов становления виртуальной идентичности приобрела в XXI в. в связи с расширением сферы жизни человека, опосредствованной цифровыми технологиями. В ряде исследований отмечены содержательные и функциональные отличительные особенности виртуальной идентичности как альтернативы тех видов идентичности, которые проявляются в реальной среде (Войскунский и др., 2013;Солдатова, Погорелов, 2018;Crisanto et al, 2022;Hu et al, 2022;Pogorelov, Rylskaya, 2022), а в других работах продемонстрировано концептуальное и функциональное сходство виртуальной идентичности с другими видами идентичности (Back et al, 2010;Granic et al, 2020;Freyth, Batinic, 2021;Shapiro, Margolin, 2014;Zimmermann et al, 2023). Подобное противоречие в понимании виртуальной идентичности, как полагаем, вызвано эмпирической многоаспектностью и разнообразием методологии исследований, что создает трудность в обобщении данных.…”
unclassified